Simulation and experimental research on electrical control anti-backlash based on a novel type of variable tooth thickness involute gear pair - Wang, Guangjian (Strojniški vestnik, 2022)
This paper presents an electrical backlash control method based on a novel variable tooth thickness involute gear pair (VTTIGP) through acceleration judgment. First, the principle, characteristics and theoretical tooth surface equation of the novel type of variable tooth thickness involute gear (VTTIG) are proposed. Compared with the traditional variable tooth thickness gear (VTTG), each transverse of the novel type of VTTIG has the same tooth root circle and the addendum circle. Therefore, there will be no interference caused by the excessive axial relative movement distance between the gear pairs when eliminating the backlash. The theoretical calculation equation of no-load transmission error (TE) and time-varying backlash for a dual-eccentric novel type of VTTIGP are deduced. Second, using the theoretical backlash equation and the eccentricities and the initial phases obtained through the experimental TE curve obtained with angular displacement sensors and the developed TE equation, the continuous backlash curve of the gear pair is obtained. Based on the RecurDyn software and its Colink control module, the co-simulation model of the novel type of VTTIGP and its backlash control system is used to explore the electrical backlash control method through acceleration judgment in the case of time-varying backlash. Finally, using angular displacement sensors and linear actuators, the experimental study on the anti-backlash control with different reversed positions under different input speeds is carried out, demonstrating that this novel electrical anti-backlash control method is effective.
Keywords: anti-backlash; časovno variabilen razstop; electrical control; električna regulacija; napaka prenosa; odprava razstopa; time-varying backlash; transmission error; variable tooth thickness gear pair; zobniška dvojica z variabilno debelino zob